2010
DOI: 10.17660/actahortic.2010.872.49
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Different Rootstocks to the Pear Tree Cultivar 'Carrick'

Abstract: Low fruiting is the main problem related to the pear production in Brazil, which makes the country one of the major pear importers. This research aimed to evaluate different rootstocks to pear tree cultivar 'Carrick' to be used in commercial orchards. The experiment was carried out in Pelotas/RS, located at latitude 31°52'00"S, longitude 52°21'24"W Greenwich and altitude of 13.24 m. The orchard was set up in 2002 with a density of 2000 trees.ha-1. The trees were conducted in slender spindler system trained on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Wertheim [19] reported that MC and BA 29 rootstocks showed higher yield efficiency than OH (Old Home) 11, OH 20, OH 33 and OHF (Old Home x Farmingdale) 333 rootstocks. As regards to yield efficiency the encountered data agree with Loreti et al [12] and Giacobbo et al [20] who analyzed different pear rootstocks and verified that the high yield efficiency is not always directly related to high production, once the rootstocks that increased production did not improve yield efficiency. These results are in general agreement with the findings of the researchers mentioned above.…”
Section: Resultssupporting
confidence: 87%
“…Wertheim [19] reported that MC and BA 29 rootstocks showed higher yield efficiency than OH (Old Home) 11, OH 20, OH 33 and OHF (Old Home x Farmingdale) 333 rootstocks. As regards to yield efficiency the encountered data agree with Loreti et al [12] and Giacobbo et al [20] who analyzed different pear rootstocks and verified that the high yield efficiency is not always directly related to high production, once the rootstocks that increased production did not improve yield efficiency. These results are in general agreement with the findings of the researchers mentioned above.…”
Section: Resultssupporting
confidence: 87%
“…This is backed up with Faust, 12 who associates the difference of leaf area development with plant development, as height, canopy volume and trunk diameter. Similar results were checked by Giacobbo et al, 4 which found that the rootstock that led to less vigorous plant also presented lower leaf areas. There were no significant differences of fresh and dry leaves weight of 'Seleta' raised on the different rootstocks ( Table 3).…”
Section: Resultssupporting
confidence: 87%
“…In this context, research work related to adaptation and behavior of pear cultivars and rootstocks has been accomplished, Giacobbo et al, 4 in a study with the cultivar Carrick found that rootstocks with larger diameter of the trunk, provide the plants, the greater weight of pruning and productive efficiency and cv. Carrick reduced in height in 44.62% when grafted on quince 'DuLot' in relation to the quince 'EMC', considered dwarf.…”
Section: Introductionmentioning
confidence: 99%
“…Giacobbo et al (2008) reported that the pruning weight of the 'Packham's Triumph' pear cultivar grafted on quince and pear rootstocks was higher on strong rootstocks than on weak rootstocks, and they emphasized that the highest pruning weight was in Smyrna and Alongado rootstocks and the lowest in Portugal rootstock. Giacobbo et al (2010) reported that the effect of rootstocks on the pruning weight of 'Carrick' pear cultivar, which they grafted on 13 different quinces and one pear rootstock, was significant. Clingeleffer et al (2019) reported that the rootstock x cultivar interaction significantly affected pruning weight.…”
Section: Resultsmentioning
confidence: 99%